Second contribution to the knowledge of water mites of the genus Monatractides K. Viets (Acari: Hydrachnidia, Torrenticolidae) from New Guinea, with descriptions of three new species - Pešić, Vladimir; Smit, Harry (Zootaxa, 2012)
New records of seven water mite species of the genus Monatractides K. Viets, 1926 (Acari: Hydrachnidia, Torrenticoli-dae) from streams in West Papua and Papua provinces, New Guinea, Indonesia are presented. Three of them, M. magnus, M. neoaustralicus and M. rivulus, are described as new for science.